Investigation on the ergonomic performance of power tiller - ASLAM SUBAIR SABITHA K.T VINIYA V.S; Dr. Geetha Susan Philip (Guide) (Tavanur 2009 Department of Farm Power Machinery and Energy)
Investigation on the ergonomic performance of power tiller
Investigation on the ergonomic performance of power tiller